Cross-species validation of conserved miR-504/PDHA1 and miR-500/EGLN2 interactions in sheep oocyte development - Junzheng Zhang; Jie Wang; Hao Li; Keyu Fu; Xu Han; Shuang Ji; Yi Jin (Theriogenology, 2026)

UAV-based measurements of methane emissions from two electrically-driven natural gas compressor stations in China - Tianran Han; Wang Tian; Yuheng Zhang; Jietao Zhou; Yanrong Yang; Keyu Chen; Lei Ren; Chuanfeng Wang; Yufei Huang; Haijiong Sun; Xinyi Chen; Chang Liu; et al. (Environmental Pollution, 2026)

Lithium-ion power batteries: From material performance to system-level safety and sustainability - Keyu Chen; JiaJia Luan; Brooke Xi; Weihua Zhang; Hanyu Jin; Daying Guo; Xi'’an Chen; Shun Wang (Chemical Engineering Journal, 2026)

Ultrafast kinetics and efficient PMS activation using a 2D calcined Co-MOF nanoconfined catalytic membrane for continuous tetracycline degradation - Jinsong He; Keyu Long; Fan Ni; Yongjia Lei; Wei Qu; Wei Shi; Yifeng Zhang; Fei Shen (Water Research, 2026)

Quantitative analysis of crust and loose layer characteristics on the surface of the earthen Great Wall - Keyu Wang; Wenwu Chen; Qiang Qi; Peiran Liu; Bobo Jia; Shuai Zhang; Quanquan Jia (CATENA, 2026)

Impacts of herbaceous plant roots on the engineering properties and erodibility assessment of the ming great wall earthen sites in the alpine and humid-cold regions - Qiang Qi; Wenwu Chen; Keyu Wang; Xiaoxiao He; Ying Wang; Fuqiang Liu; Shuai Zhang; Quanquan Jia (CATENA, 2026)

Towards complete utilization of rice husk components: A sequential process for the co-production of pectin, xylo-oligosaccharides, lignin-silica hybrid material, and fermentable sugars - Yuanxian Wu; Yuxin Xiao; Ronglian Hua; Keyu Chen; Yuanyuan Zhu; Junhua Zhang; Junjun Zhu (Biomass and Bioenergy, 2026)

Cu-doped BiOIO3 coupled with Co/Zn-ZIF for enhanced visible-light photocatalytic degradation of oxytetracycline: Synergistic effect and mechanistic insights - Maojie Zhang; Xinglin Li; Pengfei Zhu; Keyu Pu; Hongjie Xie (Journal of Environmental Chemical Engineering, 2026)

Heat transfer performance comparison and mechanism analysis of SCO2 and SCO2/R41 mixture in a double-pipe heat exchanger - Dong Wang; Keyu Sun; Hao Yu; Kangkang Zhang; Yinshuang Tao; Jun Shen (International Journal of Refrigeration, 2026)

Recent progress on hydrogen production via catalytic Auto-thermal methane Reforming: A focus on catalysts and operational parameters - Jun Wan; Peng Liu; Feiyi Zhou; Huajie Lyu; Teng Hu; Keyu Cheng; Yihong Song; Jiabiao Zou; Xiao Zhang; Saisai Lin; Chenghang Zheng; Xiang Gao (Fuel, 2026)

Modification of Lycium ruthenicum pomace dietary fibers: Enhanced physicochemical, structural, and functional properties - Huiling Li; Keyu Tian; Ruiqi Wang; Ruyu Shangguan; Jingna Yang; Nana Yang; Xintao Meng; Xiang Li; Ting Zhang; Hongjie Lei (Food Chemistry, 2026)

Multi-Year Predictability of Sandy Shoreline Change from Remote-Sensing Reconstruction and a Spatiotemporal Transformer - Keyu Tao; Fenzhen Su; Fengqin Yan; Vincent Lyne; Jiaojie Zhang (Journal of Marine Science and Engineering, 2026)
Most studies of sandy shoreline forecasting address relatively short time scales. Under limited annual observations and strong shoreline persistence, the added value of a Transformer over simple baselines and the influence of remotely sensed shoreline definitions remain insufficiently tested. Using Xichong Beach, Shenzhen, we constructed 40-year shoreline series for 80 transects from 284 quality-controlled Landsat waterlines acquired during 1986–2025. We compared a quality-controlled annual landward-envelope composite waterline with annual median waterlines and examined the effects of transect spacing and positional error on long-term change rates. We then developed a residual spatiotemporal Transformer that uses 10 years of shoreline states and historical wind–wave exposure to directly predict five future horizons, and compared it with persistence, rolling linear trend, and random forest models. The annual landward-envelope composite waterline was systematically landward of the annual median waterline (positional RMSE, 12.78 m), but their alongshore LRR patterns were strongly correlated (r = 0.982) and identified consistent major erosion–accretion zones. After Monte Carlo error propagation, the beach-mean LRR was −0.250 m yr−1 (95% interval, −0.299 to −0.203 m yr−1), whereas the direction of change remained uncertain at 39 local transects. Across 400 year–transect locations in the independent 2021–2025 evaluation period, the Transformer produced the lowest RMSE, MAE, and Dynamic RMSE (9.403, 7.399, and 12.042 m, respectively), with an RMSE skill of 27.0% relative to persistence. Environmental features yielded a small gain during rolling validation but no stable improvement in the independent evaluation period. SHAP attribution identified recent shoreline state as the dominant predictive information, followed by wind–wave exposure. Direct forecasts for 2026–2030 gave a beach-mean displacement of −8.527 m in 2030 (95% conditional residual bootstrap interval, −12.514 to −4.950 m), although every local-transect interval crossed zero. Multi-year predictability is therefore scale dependent: beach-mean trends are more resolvable, whereas local change directions remain constrained by observation error and model residuals.

Structural modifications triggered by environmental stress improve bioactivities of exopolysaccharide from endophytic bacterium Methylorubrum sp. Y19 of Taxus cuspidata - Junbo Liang; Xiaohan Zhang; Lin Zhu; Jing Luan; Keyu Sun; Jing Wang; Shuhong Ye (Food Bioscience, 2026)

From built-in LiDFP to high-stability interface: A targeted and persistent multistage strategy for lithium-rich cathode - Jin Zhu; Xiaosong Zhang; Denghui Ma; Lei Zhang; Yiyao Xiao; Keyu Zheng; Jiamin Duan; Shunjie Xu; Longhao Cao; Yinghui Li; Guanghua Guo; Xiuxia Zuo; et al. (Chemical Engineering Journal, 2026)

Spatial heterogeneity of organic carbon in muddy tidal flat sediments - Xiangxiang He; Cai Zhang; Weifang Gu; Keyu Tao; Yuwei Liu; Jiawei Ding; Xufeng Yang; Peisong Yu (Journal of Oceanology and Limnology, 2026)

Transferable and adaptable full-field structural response reconstruction from sparse sensors via GraphSAGE–LSTM neural networks - Keyu Lai; Xiaoyou Wang; Yixian Li; Hong Guan; Yiming Zhang; Yong Xia (Engineering Structures, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Functional repositioning of aerobic granular sludge as a nitrite-producing pretreatment for mainstream Anammox driven by slowly biodegradable organic matter - Zongshuo Han; Xiaoying Zheng; Jiaqing Tao; Yunqing Li; Keyu Chen; Ruijie Hu; Yifan Zhou; Yang Zhang (Process Safety and Environmental Protection, 2026)

Combining medium coalescence filtration and combined fiber coalescence: A pilot study on treating washing wastewater from shipboard EGR systems - Yu Li; Jinwei Xue; Guangyao Zhang; Yiqian Liu; Haonan Liu; Keyu Wang; Xin Han; Qiang Yang (Journal of Environmental Chemical Engineering, 2026)

Thresholds and shifting drivers for the temporal dynamics of mycorrhizal symbiosis in a temperate grassland - Qiang Dong; Xin Guo; Keyu Chen; Shijie Ren; Yu Tang; Xinling Dai; Yaoming Li; Jing Zhang; Baoming Ji (Plant and Soil, 2026)

Larix gmelinii growth limitation shifts from nitrogen availability to drought under warming and permafrost degradation - Zecheng Chen; Binqing Zhao; Wenqi Song; Hans W. Linderholm; Jan Altman; Keyu Zhang; Hanjun Dong; Xinran Huang; Haoyuan Chen; Xiaochun Wang (Global and Planetary Change, 2026)

Dietary lard promotes intramuscular fat deposition via gut microbiota-taurine axis in rabbits - Jiahao Shao; Liwen Guo; Keyu Niu; Yanjie Zhang; Herui Cao; Yongju Zhao (Food Bioscience, 2026)

Thermodynamically-driven selective phase reconstruction repairs kinetic of iron oxalate anodes for stable Li/Na storage - Yichong Kong; Binxin Yu; Keyu Zhang; Binbin Li; Bo Jin; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2026)

RoofX-Net: A tailored approach to accurate multi-type rooftop segmentation in remote sensing images using edge and scale awareness - Keyu Chen; Tianlei Wang; Zhiyou Yang; Fan Li; Ma Luo; Ruoning Zhang; Hong Qu; Wenyu Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Low‑intensity aeration enhances algal–bacterial synergy to improve nitrogen removal from wastewater with low carbon-to-nitrogen ratio - Yunqing Li; Xiaoying Zheng; Ruijie Hu; Jiaqing Tao; Zongshuo Han; Keyu Chen; Yifan Zhou; Yang Zhang; Wei Chen (Bioresource Technology, 2026)

Bacillus Cereus C3 Addition Facilitates Carbohydrate Degradation and Earthworm Growth During Vermicomposting of Sewage Sludge - Tiantian Tian; Xinge Cui; Wenxing He; Keyu Liu; Jiran Zhang; Shimin Zhang; Xitian Yang; Kun Wu; Xianqin Jiao; Shuxia Xu (Water, Air, & Soil Pollution, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Developmental stage-specific disruption of iron allocation by a ZmYSL2 mutation in maize - Yikai Wang; Kunfeng Zhang; Chuang An; Jiayi Liu; Hongmei Hu; Duo Shi; Jiaxin Shi; Keyu Zhao; Dan Liu; Ling Wu; Xiao Zhang; Bowen Luo; et al. (Planta, 2026)

Comprehensive chemical molecular characterization of petroleum-contaminated soils: Unraveling physical migration and biotransformation processes in the vadose and saturated zones - Wang Yu; Yuruo Wan; Jiuhao Song; Keyu Duan; Junjie Guan; Qi Gao; Yuping Zhang; Jianhui Ma; Jie Ma (Environmental Pollution, 2026)

Defect-triggered S-scheme heterojunction coupled with single-molecular catalytic centers towards selective photocatalytic CO2 reduction to CO - Keyu Cui; Yujia Wang; Xingjing Zhang; Jiaming Li; Chunbo Liu; Liqiu Zhang; Hongjun Dong; Chunmei Li (Chemical Engineering Journal, 2026)

Ionic liquid-mediated concurrent oxygen vacancies and N-doped carbon in hierarchical TiP2O7 for lithium storage - Wenfang Cui; Yongmei Sun; KeYu Zhang; Chengcheng Shi; Peng Fu; Mei Ma (Chemical Engineering Journal, 2026)

Apoptotic extracellular vesicles: unveiling mechanisms, diverse functions, and biomedical implications - Xuan Li; Keyu Wang; Caining Wen; Haorui Li; Limei Xu; Yuanmin Zhang; Xiao Xu; Yujie Liang (Apoptosis, 2026)

Triploid induction by hydrostatic pressure in female Megalobrama amblycephala × male Culter alburnus hybrids: effects on somatic growth enhancement and sterility - Zaozao Guo; Lianghua Zhang; Chao Ren; Keyu Su; Xiangsheng Yu; Guodong Zheng; Shuming Zou (Aquaculture, 2026)

Quantifying the effect of chlorite on reservoir quality and CO2 sequestration in deep saline aquifers from the permian tight sandstone reservoir in the ordos basin, China - Yaxin Shang; Keyu Liu; Ziyi Wang; Bo Zhang (Marine and Petroleum Geology, 2026)

Synergistic pathways for regional energy transition and water conservation: insights from the receiving areas of the South-to-North Water Diversion Middle Route - Weiwen Liu; Chao Ma; Haixing Gou; Ximeng Xu; Ruixin Zhang; Weiren Huang; Keyu Guo (Journal of Hydrology, 2026)

Soft-chemical topotactic pathway to (001)-faceted hollandite K-Fe-Ti oxides with accelerated Li+ migration - Xing Wang; Ling Che; Zihao Li; Zhigao Chen; Xingang Kong; Kun Zhang; Keyu Xie (Chemical Engineering Journal, 2026)

ACSL4 Inhibition by AS-252424 Protects Visual Function by Suppressing RGC Ferroptosis After Retinal Ischemia Reperfusion Injury - Keyu Liu; Zihao Lin; Wu Xiang; Jiayi Zhang; Xiaofeng Wu; Chenzhao Ma; Yantao Wei; Jiawei Wang; Jianqiao Li (Molecular Neurobiology, 2026)

Regional disparities and provincial peak trajectories of transportation carbon emissions in Western China - Zhixiao Zhang; Keyu Wen; Hao Gong; Yugang Wang; Liuhui Zhao; Dongmei Wang; Zhengjun Gong (Transportation Research Part D: Transport and Environment, 2025)

Deciphering gut microbial dynamics and multi-omics changes in yogurt-based dietary interventions - Qiuwen He; Yaru Sun; Hao Jin; Lai-Yu Kwok; Teng Ma; Keyu Quan; Yalin Li; Xuan Shi; Zhihong Sun; Heping Zhang (Science Bulletin, 2025)

Exogenous melatonin regulates hormone metabolism involved in delaying the ripening process in cherry tomato fruit during storage - Hang Zhang; Yue Wang; Jianhui Cheng; Wenbo Lei; Keyu Xu; Lilai Yin; Chen Huan; Shuling Shen; Lanying Yao; Xiaolin Zheng (Postharvest Biology and Technology, 2025)

Guttulatic calcite evidence for carboniferous icehouse climate in the Ordos Basin, North China Craton - Jiaqi Yang; Zhiliang He; Juntao Zhang; Keyu Liu; Macro Brandano; Jingbin Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Spatial accessibility to public electric vehicle charging infrastructure and multi-mechanism process of regional inequity in Greater Bay Area, China - Xing Gao; Huizi Wang; Ying Zhang; Keyu Zhai; Meiling Wu (Journal of Transport Geography, 2025)

Graphite-phase carbon nitride composites: Pioneering advancements and future prospects in capacitive desalination - Feifan Zhang; Hongying Lv; Yuying Pan; Yutao Chen; Keyu Hou; Zhiheng Wang; Jiuwen Sun; Hong Chen; Junli Pan; Shouqiang Huang (Journal of Environmental Management, 2025)

Cumulative droughts and legacy effects decreased long-term growth resilience in Pinus massoniana in the middle Dabie Mountains - Yameng Liu; Jinkuan Li; Jianfeng Peng; Jiaxin Li; Xiaoxu Wei; Keyu Zhang (Dendrochronologia, 2025)

Architectural design of multidimensional carbonaceous structures: Synergistic pathways enabling high-energy silicon-based anodes - Wendi Chen; Lingjun Guo; Ruonan Zhang; Guangyao Liu; Yue Ma; Dian Jia; Hejun Li; Keyu Xie (Chemical Engineering Journal, 2025)

PRKAG1 mediates the anti-Japanese encephalitis virus effect of Nitazoxanide through autophagy - Hui Ma; Xiaoyang Wang; Chunmei Wang; Wenchong Ye; Wen Zhou; Fengcai Zou; Keyu Zhang (Veterinary Microbiology, 2025)

Design of amides and long-chain alkyl alcohols for high selectivity recovery of titanium and iron from ilmenite - Keyu Zhu; Qinqin Yu; Guokang Hu; Changchang Chen; Yanni Li; Jiacan Tang; Weiwei Zhang (Minerals Engineering, 2025)

Dynamic interactions in energy-water nexus: risk-based framework for balancing electricity expansion and water resource sustainability - Haixing Gou; Chao Ma; Ximeng Xu; Weiwen Liu; Ruixin Zhang; Weiren Huang; Keyu Guo (Journal of Hydrology, 2025)

Metagenomic analysis of bacterial fitness and plasmids carrying blaTEM-1 and virulence genes before and after cleaning and disinfection in pig slaughterhouses - Shanshan Chu; Yan Chen; Zhuoqun Xu; Jie Zhou; Keyu Li; Qi Zhang; Min Qian; Jianzhong Han; Daofeng Qu (Journal of Hazardous Materials, 2025)

Regulation of astaxanthin accumulation in Phaffia rhodozyma under titanium dioxide and rapeseed oil stress by amino acid metabolism - Meizhen Liu; Tiantian Han; Lu Luo; Ying Zhang; Gaofeng Yuan; Xubo Fang; Keyu Dong; Jing Zhang; Xiaoe Chen (Food Chemistry, 2025)

Abiotic stress-induced resveratrol accumulation in peanut sprouts: methods and research frontiers - Wangqi Zhang; Yihan Zhang; Shuang Wang; Keyu Wei; Shengdan Liu; Mouyan Liu; Huazhong Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Dynamic quantitative characterization method for the weathering degree of earthen heritage sites surfaces based on 3D scanning technology and wavelet transform theory - Wenwu Chen; Qiang Qi; Keyu Wang; Shuai Zhang; Zhiqian Guo; Kebing Ren; Haitao Yan (Bulletin of Engineering Geology and the Environment, 2025)

Evaluating Gas Saturation in Unconventional Gas Reservoirs Using Acoustic Logs: A Case Study of the Baiyun Depression in the Northern South China Sea - Jiangbo Shu; Changchun Zou; Cheng Peng; Liang Xiao; Keyu Qiao; Xixi Lan; Wei Shen; Yuanyuan Zhang; Hongjie Zhang (Journal of Marine Science and Engineering, 2025)
Shallow gas is an unconventional natural gas resource with great potential and has received growing attention recently. Accurate estimation of gas saturation is crucial for reserves assessments and for development program formulations. However, such reservoirs are characterized by weak diagenesis, a high clay content, and low resistivity. These properties pose significant challenges for saturation evaluations. To address the challenge of insufficient accuracy in evaluating the saturation of gas-bearing reservoirs, we propose an acoustic-based saturation evaluation method. In this study, a shallow unconsolidated rock physics model is first constructed to investigate the effect of variations in the gas saturation on elastic wave velocities. The model especially considers the patchy distribution of fluids within pores. In addition, we propose an iterative algorithm based on the updated relationship between porosity and gas saturation by introducing a correction term for the saturation to the density porosity, and successfully apply it to the logging data collected from the shallow gas reservoirs in the Pearl River Mouth Basin of the South China Sea. It is evident from the results that the saturation derived from the array acoustic logs is comparable to that obtained from the resistivity logs, with a mean absolute error of less than 6%. Additionally, it is also consistent with the drill stem test (DST) data, which further verifies the validity and reliability of this method. This study provides a novel non-electrical method for estimating the saturation of shallow gas reservoirs, which is essential to promote the evaluation of unconsolidated sandstone gas reservoirs.

Short-term emissions effect of rainfall erosion on soil CO2 in red soil sloped farmland in southern China - Keyu Yan; Xiaohan Mei; Chuan Zhang; Yanmei Hu; Daoxiang Wang; Zhengfa Chen; Xiaofeng Yang; Yanrui Shao; Yanjun Mao (Soil and Tillage Research, 2025)

Transgenerational effects and mechanisms of nano-SiO2 on pulmonary - Jiangliang Chu; Chengzhi Liu; Shuang Chen; Yifan Yang; Keyu Zhang; Yiping Fu; Beilei Yuan; Zhe Wang (Reproductive Toxicology, 2025)

Ecosystem engineering and global changes are increasingly enhancing China’s terrestrial carbon sinks - Mengyu Zhang; Honglin He; Li Zhang; Xiaoli Ren; Liang Shi; Guirui Yu; Zhong’en Niu; Keyu Qin; Tiecheng Li (Resources, Conservation and Recycling, 2025)

Effect and mechanism of Rice-Solanum nigrum L. rotation system inoculated with sulfate-reducing bacteria (SRB) and sulfur-oxidizing bacteria (SOB) for the remediation of Cd-contaminated paddy soil - Dan Zhang; Yipeng Gong; Rui Qin; SHAH ZAIB; Keyu Shang; Jia Xia; Liting Zhou; Yifei Xie (Journal of Hazardous Materials, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

Groundwater leakage of an endorheic basin with extensive permafrost coverage in the western Mongolian Plateau - Shun Hu; Cenhanyi Hu; Keyu Meng; Yinghui Long; Jing Zhang; Mingxin Wang; Linglin Zeng; Zilong Liao (Journal of Hydrology, 2025)

Regional NDVI reconstruction based on tree-ring width of Pinus massoniana Lamb. in the north-south transition zone of China - Kunyu Peng; Yameng Liu; Keyu Zhang; Jiaxin Li; Jinkuan Li; Xiaoxu Wei; Mengyu Wang; Jianfeng Peng (Dendrochronologia, 2025)

Enhanced rare-earth doped mechanoluminescent piezoelectric heterojunction semiconductors through interface engineering with tunable photonic responses for advanced sensing applications - Fanlei Qin; Yujie Chen; Qinglong Hu; Keyu Han; Zhen Xiao; Yang Zhang; Gongxun Bai (Chemical Engineering Journal, 2025)

p-chlorophenylalanine treatment accelerates tomato fruit ripening through hormone synthesis and glycolytic pathway during storage - Keyu Xu; Ran Yan; Hang Zhang; Lilai Yin; Wenbo Lei; Jianhui Cheng; Chen Huan; Yan Liu; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2025)

Climate change and social turmoil in the late Qing Dynasty revealed by tree rings - Jinkuan Li; Jiaxin Li; Yameng Liu; Keyu Zhang; Xiaoxu Wei; Mengyu Wang; Jianfeng Peng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Temporal-spatial analysis and geological interpretation of groundwater dynamics in a marine aquifer - Keyu Gong; Zhang Wen; Qinghua Li; Qi Zhu (Journal of Hydrology, 2025)

The potentials of uncertainty analysis and Bayesian optimization in HONO source modeling diagnosis and improvement - Jinlong Zhang; Wending Wang; Keyu Zhu; Zhijiong Huang; Li Sheng; Songdi Liao; Xin Yuan; Yanan Hu; Jiangping Liu; Mengxue Tang; Xiaofeng Huang; Jie Li; et al. (Environmental Research, 2025)

Oxygen vacancies and Li+ pre-embedding for magnesium storage in Anatase TiO2 toward magnesium/lithium hybrid batteries - Haofei Du; Xueyang Hou; Fan Cheng; Yifan Liu; Zhao Fang; Keyu Xie; Ling Zhang (Chemical Engineering Journal, 2025)

Nitrogen level determines arbuscular mycorrhizal fungi nitrogen uptake rate of Stipa purpurea in alpine steppe - Jiahui Sun; Yu Tang; Keyu Chen; Shijie Ren; Hailan Shi; Qiang Dong; Junfu Dong; Lin Zhang; Xiaoyong Cui; Yanfen Wang; Baoming Ji; Jing Zhang (Plant and Soil, 2025)

A genomic compendium of cultivated food-derived lactic acid bacteria unveils their contributions to human health - Hao Jin; Keyu Quan; Lijun You; Lai-Yu Kwok; Teng Ma; Yalin Li; Xuan Shi; Xin Su; Ruirui Lv; Zhihong Sun; Wenjun Liu; Heping Zhang (Science Bulletin, 2025)

Construction and efficacy of a recombinant QX-like infectious bronchitis virus vaccine strain - Lin Lin; Keyu Feng; Guanming Shao; Shiying Gong; Tongfei Liu; Feng Chen; Xinheng Zhang; Qingmei Xie (Virus Genes, 2025)

Paleoenvironmental evolution and isotopic stratigraphy of the Lower Cambrian in the Tarim Basin: Implications for global paleoenvironmental reconstruction - Weijing Liu; Keyu Liu; Yaxin Shang; Yifan Zhang; Jianliang Liu; Kuanhong Yu (Gondwana Research, 2025)

Diagenetic controls on sweet spots pore types and reservoir quality of Permian tight sandstones in the Ordos Basin, China - Yaxin Shang; Keyu Liu; Ziyi Wang; Bo Zhang (Marine and Petroleum Geology, 2025)

Corrigendum to “Gastrointestinal digestibility of micellar casein dispersions: Effects of caprine vs bovine origin, and partial colloidal calcium depletion using in vitro digestion models for the adults and elderly” [Food Chem. 416 (2023) 135865] - Jie Zhang; Dasong Liu; Yunqi Xie; Jiajie Yuan; Keyu Wang; Xiumei Tao; Yacine Hemar; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Chemistry, 2025)

Study of the early regulatory mechanism of the Pichia kudriavzevii-induced resistance response in cherry tomato fruits - Shanwei Zhou; Xuanqing Zhang; Naixuan Han; Keyu Sun; Xiaoyu Liu; Jun Guo; Qiong Tang (Food Bioscience, 2025)

Whether to continue combining carbapenems to treat carbapenem-resistant Acinetobacter baumannii nosocomial pneumonia in critically ill patients: a retrospective efficacy and safety analysis - Cheng Shiqi; Wang Chuhui; Zhang Yijing; Qiu Yulan; Chen Jiaojiao; Chen Keyu; Shi Qindong; Zeng Xiaoyan; Dong Yalin (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The impacts of China’s sustainable financing policy on environmental, social and corporate governance (ESG) performance - Haoyu Li; Xing Gao; Xingman Zhang; Keyu Zhai; Yantao Ling; Mengqiu Cao (Environment, Development and Sustainability, 2025)

Cost effective selective separation of indium and germanium from zinc processing waste leach liquor using D2EHPA-YW100 synergistic system and selective stripping with HCl and NH4F - Chen Wang; Junxian Hu; Keyu Zhang; Shaoze Zhang; Yin Li; Yaochun Yao (Hydrometallurgy, 2025)

Stability of China's terrestrial ecosystems carbon sink during 2000-2020 - Liang Shi; Honglin He; Li Zhang; Junbang Wang; Xiaoli Ren; Guirui Yu; Peng Hou; Jixi Gao; Bin Chen; Keyu Qin; Lili Feng; Shaoqiang Wang; et al. (Resources, Conservation and Recycling, 2025)

Integration of transcriptomics and metabolomics reveal cytotoxic mechanisms of Polyethylene terephthalate microplastics in BEAS-2B cells - Jiangliang Chu; Yifan Yang; Keyu Zhang; Yiping Fu; Beilei Yuan (Food and Chemical Toxicology, 2025)

Saline soil improvement promotes the transformation of microbial salt tolerance mechanisms and microbial-plant-animal ecological interactions - Keyu Yao; Guanghao Wang; Wen Zhang; Qiang Liu; Jian Hu; Mao Ye; Xin Jiang (Journal of Environmental Management, 2024)

Crystal and micro-nano structure bidirectional regulation of iron oxalate for high-lithium storage and ultralong-cycling life via ultrasound assistance - Qing Zhao; Keyu Zhang; Geng Gao; Bo Jin; Guangping Zi; Rui Yan; Binbin Li; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

The modulation of proteomics and antioxidant stress is involved in the effect of nitazoxanide against Japanese encephalitis virus in vitro - Yu Su; Yanping Wang; Chengeng Xiong; Xiaoyang Wang; Chunmei Wang; Wen Zhou; Donghai Zhou; Keyu Zhang (Veterinary Microbiology, 2024)

Spatial mapping of greenhouse gases using a UAV monitoring platform over a megacity in China - Tianran Han; Conghui Xie; Yanrong Yang; Yuheng Zhang; Yufei Huang; Yayong Liu; Keyu Chen; Haijiong Sun; Jietao Zhou; Chang Liu; Junfei Guo; Zhijun Wu; et al. (Science of The Total Environment, 2024)

Optimizing pollen germination and subcellular dynamics in pollen tube of Torreya grandis - Shuai Hu; Chengqiao Wang; Rui Zhang; Yanli Gao; Keyu Li; Jinbo Shen (Plant Science, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Development of a CRISPR/Cas12a-based method to detect invasive aquatic species - Minlin Zhang; Xiaoling Zuo; Jiantao Liang; Keyu Lu; Liyun Wei; Xu Yan; Huihong Zhao; Songyong Gan; Jinhui Wu; Qing Wang (Aquaculture, 2024)

Wind erosion prevention and trans-boundary ecosystem service payments in the Hunshandake region - Mengdong Huang; Yu Xiao; Changshun Zhang; Lin Zhen; Keyu Qin; Jingya Liu; Jie Xu; Shuang Gan; Jia Liu; Chunxia Lu; Gaodi Xie (Journal of Cleaner Production, 2024)

Increased ecological land and atmospheric CO2 dominate the growth of ecosystem carbon sinks under the regulation of environmental conditions in national key ecological function zones in China - Mengyu Zhang; Honglin He; Li Zhang; Guirui Yu; Xiaoli Ren; Yan Lv; Zhong'en Niu; Keyu Qin; Yanni Gao (Journal of Environmental Management, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Isolation of a facultative methanotroph Methylocystis iwaonis SD4 from rice rhizosphere and establishment of rapid genetic tools for it - Yinghui Wang; Yuying Wang; Keyu Zhou; Haili Zhang; Minggen Cheng; Baozhan Wang; Xin Yan (Biotechnology Letters, 2024)

May–June relative humidity variation recorded by tree ring widths of Pinus armandii Franch since 1863 in the Funiu Mountains, central China - Jinkuan Li; Kunyu Peng; Xiaoxu Wei; Yameng Liu; Jiaxin Li; Meng Peng; Xuan Li; Keyu Zhang; Jianfeng Peng (Quaternary International, 2024)

Boosting activity on CoFe layered double hydroxide by doping and heterostructure as a bifunctional electrocatalyst for efficient overall water splitting - Jian Tang; Junxian Hu; Xuanli Chen; Bin Yang; Keyu Zhang; Yin Li; Yaochun Yao; Shaoze Zhang (Fuel, 2024)

Investigation on Phenomics of Traditional Chinese Medicine from the Diabetes - Boxun Zhang; Lijuan Zhou; Keyu Chen; Xinyi Fang; Qingwei Li; Zezheng Gao; Fengmei Lian; Min Li; Jiaxing Tian; Linhua Zhao; Xiaolin Tong (Phenomics, 2024)
With thousands of years of application history, traditional Chinese medicine (TCM) has unique advantages in the prevention of various chronic diseases, and in recent years, the development of TCM has presented a situation where opportunities and challenges coexist. Phenomics is an emerging area of life science research, which has numerous similarities to the cognitive perspective of TCM. Thus, how to carry out the interdisciplinary research between TCM and phenomics deserves in-depth discussion. Diabetes is one of the most common chronic non-communicable diseases around the world, and TCM plays an important role in all stages of diabetes treatment, but the molecular mechanisms are difficult to elucidate. Phenomics research can not only reveal the hidden scientific connotations of TCM, but also provide a bridge for the confluence and complementary between TCM and Western medicine. Facing the challenges of the TCM phenomics research, we suggest applying the State-target theory (STT) to overall plan relevant researches, namely, focusing on the disease development, change trends, and core targets of each stage, and to deepen the understanding of TCM disease phenotypes and the therapeutic mechanisms of herbal medicine.

Corrigendum to “An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features” [Fuel 352 (2023) 128753] - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2024)

Porous rod-like structured ternary nitride heterocatalyst Co3Mo3N/Ni3Mo3N for efficient and stable hydrogen evolution reaction - Jian Tang; Shaoze Zhang; Yixing Zeng; Bin Yang; Keyu Zhang; Yin Li; Yaochun Yao; Junxian Hu (Chemical Engineering Journal, 2024)

Effect of hydrothermal carbonization on pyrolysis behavior, nutrients and metal species distribution in municipal sludge - Changhao Liu; Zhengbo Yue; Ding Ma; Keyu Li; Zhilin Xie; Tianqin Zhang; Jin Wang (Bioresource Technology, 2024)

Effects of natural extract from medicinal herbs on broilers experimentally infected with Eimeria tenella - Yuanyuan Jiang; Yujuan Zeng; Keyu Chen; Haoran Cheng; Songjiang Dai; Xuexue Deng; Long Wang; Jinqiu Liao; Ruiwu Yang; Li Zhang (Veterinary Parasitology, 2024)

Moderate grazing increased carbon, nitrogen and phosphorus storage in plants and soil in the Eurasian meadow steppe ecosystem - Miao Wang; Chu Zhang; Sisi Chen; Yu Zhang; Tianqi Yu; Xiaojuan Xue; Lianhai Wu; Wenneng Zhou; Xiangjun Yun; Ruirui Yan; Keyu Bai (Science of The Total Environment, 2024)

Tectono-sedimentary evolution of the southwestern Tarim Basin in the cretaceous in response to basin-range coupling: New insights from basin and landscape dynamics modeling - Jia Chang; Keyu Liu; Wenfang Yuan; Jianliang Liu; Liqiang Zhang; Cai Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The fundamentals, progress, and perspectives of transition-metal dichalcogenides (TMDs) applied in advanced oxidation processes - Hao Huang; Mengyang Zhang; Keyu Xu; Yanling Zhuang; Yue Li; Longlu Wang (Chemical Engineering Journal, 2024)

Bufogarlides A-C, three new bufadienolides with Δ 14,15 double bond from the skins of Bufo bufo gargarizans - Lingjie Meng; Qinghong Kong; Jianxun Xie; Feng Pan; Keyu Lu; Sanhua Li; Yiling Li; Di Zhang; Yun Liu (Natural Product Research, 2024)

Ibuprofen inhibits anaplastic thyroid cells in vivo and in vitro by triggering NLRP3-ASC-GSDMD-dependent pyroptosis - Haohao Guo; Runsheng Ma; Yifei Zhang; Keyu Yin; Gongbo Du; Fanxiang Yin; Hongqiang Li; Ziyang Wang; Detao Yin (Inflammopharmacology, 2024)
Pyroptosis is a novel type of proinflammatory programmed cell death that is associated with inflammation, immunity, and cancer. Anaplastic thyroid carcinoma (ATC) has a high fatality rate, and there is no effective or standard treatment. The disease progresses rapidly and these tumors can invade the trachea and esophagus, leading to breathing and swallowing difficulties. Hence, new treatment methods are greatly needed. Ibuprofen is a common drug that can exert antitumor effects in some cancers. In this study, we demonstrated in vitro and in vivo that ibuprofen can induce ATC pyroptosis. Hence, we treated C643 and OCUT-2C ATC cells with ibuprofen and found that several dying cells presented the characteristic morphological features of pyroptosis, such as bubble-like swelling and membrane rupture, accompanied by activation of ASC and NLRP3 and cleavage of GSDMD. Along with the increased release of LDH, ibuprofen treatment promoted apoptosis and inhibited viability, invasion, and migration. However, overexpression of GSDMD significantly inhibited ibuprofen-induced pyroptosis. In vivo, research has demonstrated that thyroid tumor growth in nude mice can be suppressed by ibuprofen-induced pyroptosis in a dose-dependent manner. In this research, we explored a new mechanism by which ibuprofen inhibits ATC growth and progression and highlighted its promise as a therapeutic agent for ATC.

Long-term grazing exacerbates soil microbial carbon and phosphorus limitations in the desert steppe of Inner Mongolia - A study based on enzyme kinetics - Shaoyu Li; Bin Zhang; Yanan Li; Tianqi Zhao; Jiahua Zheng; Jirong Qiao; Feng Zhang; Carlo Fadda; Devra Jarvis; Nadia Bergamini; Keyu Bai; Zongwen Zhang; et al. (Applied Soil Ecology, 2024)

How does grazing pressure affect feed intake and behavior of livestock in a meadow steppe in northern China and their coupling relationship - Tianqi Yu; Ruirui Yan; Chu Zhang; Sisi Chen; Zhitao Zhang; LeiFeng Guo; Tianci Hu; Chengxiang Jiang; Miao Wang; Keyu Bai; Wenneng Zhou; Lianhai Wu (Science of The Total Environment, 2024)

The boundary between the Middle and Upper Cambrian strata in the Tarim Basin, NW China: Regional to global SPICE event correlation - Yaxin Shang; Keyu Liu; Zhiqian Gao; Chenjia Zhang; Ziyi Wang (Journal of Asian Earth Sciences, 2024)

Revealing the infiltration process and retention mechanisms of surface applied free DNA tracer through soil under flood irrigation - Geng Liu; Linxi Guo; Chaozi Wang; Jiarong Liu; Zengjie Hu; Helen E. Dahlke; En Xie; Xiao Zhao; Guanhua Huang; Jun Niu; Keyu Fa; Chenglong Zhang; et al. (Science of The Total Environment, 2023)

Long-term fencing can't benefit plant and microbial network stability of alpine meadow and alpine steppe in Three-River-Source National Park - Keyu Chen; Sen Xing; Hailan Shi; Yu Tang; Mingxin Yang; Qiang Gu; Yaoming Li; Jing Zhang; Baoming Ji (Science of The Total Environment, 2023)

Enhancing the sewage treatment effect, reducing membrane fouling, and increasing microbial community diversity by a novel biofiller-carrying functional bacteria Rhodococcus sp. CPZ24 in a moving bed biofilm reactor - Peizhen Chen; Dongkai Chen; Bo Yang; Keyu Zhang; Shaopeng Li (Journal of Water Process Engineering, 2023)

Seasonal peak and the role of local weather in schizophrenia occurrence: A global analysis of epidemiological evidence - Jihong Hu; Yufan Feng; Hong Su; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Keyu Wu; Mohammad Zahid Hossain; Yunquan Zhang; Kejia Hu; et al. (Science of The Total Environment, 2023)

The iLABdb: a web-based integrated lactic acid bacteria database - Hao Jin; Teng Ma; Lin Chen; Lai-Yu Kwok; Keyu Quan; Yalin Li; Zeng Zhang; Tong Chen; Jiachao Zhang; Zhihong Sun; Heping Zhang (Science Bulletin, 2023)

An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2023)

Biosynthesis of maltodextrin-derived glucan dendrimer using microbial branching enzyme - Yimei Chen; Xiuting Hu; Keyu Lu; Tao Zhang; Ming Miao (Food Chemistry, 2023)

Proteomic profiling of purified avian leukosis virus subgroup J particles - Sheng Chen; Yiming Yan; Liguo Gao; Shuang Gao; Keyu Feng; Hongxin Li; Xinheng Zhang; Weiguo Chen; Feng Chen; Qingmei Xie (Veterinary Microbiology, 2023)

Targeting gut microbiota and metabolism as the major probiotic mechanism - An evidence-based review - Teng Ma; Xin Shen; Xuan Shi; Hafiz Arbab Sakandar; Keyu Quan; Yalin Li; Hao Jin; Lai-Yu Kwok; Heping Zhang; Zhihong Sun (Trends in Food Science & Technology, 2023)

Gastrointestinal digestibility of micellar casein dispersions: Effects of caprine vs bovine origin, and partial colloidal calcium depletion using in vitro digestion models for the adults and elderly - Jie Zhang; Dasong Liu; Yunqi Xie; Jiajie Yuan; Keyu Wang; Xiumei Tao; Yacine Hemar; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Chemistry, 2023)

Using starch structure to choose rices with an optimal combination of palatability and digestibility - Jihui Zhu; Keyu Tao; Sangeeta Prakash; Changquan Zhang; Robert G. Gilbert; Qiaoquan Liu (Food Hydrocolloids, 2023)

Achieving high yield and nitrogen agronomic efficiency by coupling wheat varieties with soil fertility - Keyu Ren; Minggang Xu; Rong Li; Lei Zheng; Huiying Wang; Shaogui Liu; Wenju Zhang; Yinghua Duan; Changai Lu (Science of The Total Environment, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

Differential hydrocarbon generation and evolution of typical terrestrial gas-prone source rocks: An example from the Kuqa foreland basin, NW China - Jianliang Liu; Xianzhang Yang; Keyu Liu; Zhenping Xu; Kun Jia; Lu Zhou; Hongxing Wei; Liang Zhang; Shaojun Wu; Xinzhuo Wei (Marine and Petroleum Geology, 2023)

The influence of CO2 partial pressure on the stability of dawsonite-based on water-rock physical experiment and numerical simulation - Fulai Li; Chun Zhang; Kaining Wang; Wenkuan Ma; Jianlei Yang; Qizhen Du; Shaogui Deng; Keyu Liu (Applied Geochemistry, 2023)

Geostatistical simulations of the spatial variability of hydraulic conductivity in an alluvial-marine sedimentary system in Beihai City, China - Keyu Gong; Zhang Wen; Qinghua Li; Qi Zhu (Journal of Hydrology, 2023)

Decalcification strongly affects in vitro gastrointestinal digestion of bovine casein micelles under infant, adult and elderly conditions - Keyu Wang; Dasong Liu; Xiumei Tao; Jie Zhang; Thom Huppertz; Joe M. Regenstein; Xiaoming Liu; Peng Zhou (Food Hydrocolloids, 2023)

Plant community and soil available nutrients drive arbuscular mycorrhizal fungal community shifts during alpine meadow degradation - Keyu Chen; Jing Zhang; Muhammad Atif Muneer; Kai Xue; Haishan Niu; Baoming Ji (Fungal Ecology, 2023)

Cross-sectional Exploration of the Relationship Between Glutamate Abnormalities and Tic Disorder Severity Using Proton Magnetic Resonance Spectroscopy - Juanjuan Hao; Xin Zhang; Ying Liu; Zhongyang Zhang; Keyu Jiang; Xiao-Yong Zhang; Min Wu (Phenomics, 2023)

A systematic review and meta-analysis of air pollution and angina pectoris attacks: identification of hazardous pollutant, short-term effect, and vulnerable population - Min Yang; Keyu Wu; Qiyue Wu; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Junwen Tao; Hao Zheng; Mohammad Zahid Hossain; Wenyi Zhang; Ning Wang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Abnormal ambient temperature change increases the risk of out-of-hospital cardiac arrest: A systematic review and meta-analysis of exposure types, risk, and vulnerable populations - Qiyue Wu; Min Yang; Keyu Wu; Hong Su; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Thi Anh Thu Dang; Mohammad Zahid Hossain; et al. (Science of The Total Environment, 2023)

Associations between exposure to brominated flame retardants and metabolic syndrome and its components in U.S. adults - Zhiqiang Che; Huixun Jia; Renjie Chen; Keyu Pan; Zhe Fan; Chang Su; Zhenyu Wu; Tao Zhang (Science of The Total Environment, 2023)

Degradation of lomefloxacin by MoS2/MIL-53(Fe, Cu) catalyst in heterogeneous electro-Fenton process - Lei Fang; Guojian Wu; Keyu Yao; Dongyang Zhang; Yongchao Zhou (Environmental Science and Pollution Research, 2023)

Carbazole and polyhalogenated carbazoles in the marine environment around the Zhoushan Archipelago: Distribution characteristics, environmental behavior, and sources - Zhaochao Deng; Songtao Hu; Leiming Tang; Lingbo Jiang; Junyu He; Keyu Shen; Yongjiu Xu; Rijin Jiang; Tiejun Li; Chunlei Chen; Bairu Chen; Hanghai Zhou; et al. (Journal of Hazardous Materials, 2023)

Responses of grassland productivity to mowing intensity and precipitation variability in a temperate steppe - Feng Zhang; Jonathan A. Bennett; Bin Zhang; Tianqi Zhao; Keyu Bai; Mengli Zhao; Guodong Han (Oecologia, 2023)

A three-dimensional experimental study on bank retreat: The coupled role of seepage and surface flow - Keyu Wang; Zheng Gong; Kun Zhao; Shuai Tang; Kaili Zhang (Frontiers in Marine Science, 2022)
The coupled role of seepage and surface flow on bank retreat has long been neglected, partly due to the concealment and complexity of seepage erosion. To fill this gap, we set up a three-dimensional laboratory experiment to explore bank retreat process in response to seepage and surface flow. During each experiment, we measured the changes of total soil stress, matric suction, and water content within the bank, as well as flow velocity and suspended sediment concentration near the bank. Results show that a rapid decrease in matric suction, the bank toe undercutting consequent to seepage erosion, the formation of tension crack on the bank top, and the occurrence of toppling or shear failure is the typical sequence of the observed bank retreat process under seepage flow. The inclusion of surface flow erodes slump blocks and so promotes cantilever formation, leading to additional bank failure. Compared with the case where only seepage is considered, the frequency of toppling failure under the coupled effect of seepage and surface flow decreases, but the contribution to the bank retreat increases by 37 %. The time taken to collapse in three-dimensional experiments is at least 1.5 h earlier than that of two-dimensional experiments, indicating the importance of preferential flow pathways of seepage. Overall, this research illustrates how surface flow interacts with seepage flow to control bank retreat process and is indeed a first step toward a fully understanding of multifactor-driven bank retreat.

Fine mapping of powdery mildew resistance gene MlWE74 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) in an NBS-LRR gene cluster - Keyu Zhu; Miaomiao Li; Haibin Wu; Deyun Zhang; Lingli Dong; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Guanghao Guo; Huaizhi Zhang; Panpan Zhang; et al. (Theoretical and Applied Genetics, 2022)

Resistance of blended alkali-activated fly ash-OPC mortar to mild-concentration sulfuric and acetic acid attack - Keyu Chen; Dazhi Wu; Sijia Fei; Chonggen Pan; Xinyuan Shen; Chaoxia Zhang; Juntao Hu (Environmental Science and Pollution Research, 2022)

Occurrence and distribution characteristics of antibiotic resistance genes in sediments between urban and rural of the Liaohe River Basin, China - Guangshui Na; Keyu Zhang; Hui Gao; Ruijing Li; Shuaichen Jin; Fuqiang Zhao; Haibo Zhang; Shisheng Li (Environmental Science and Pollution Research, 2021)

Revisiting Rhenium-Osmium Isotopic Investigations of Petroleum Systems: From Geochemical Behaviours to Geological Interpretations - Shao-Jie Li; Xuan-Ce Wang; Simon A. Wilde; Zhuyin Chu; Chaofeng Li; Sheng He; Keyu Liu; Xingzhi Ma; Yuxiang Zhang (Journal of Earth Science, 2021)

Optimized production and characterization of cation-independent bioflocculant produced by Klebsiella sp. 59L - Keyu Fang; Boji Wang; Yao Zhang; Hongjing Li (Environmental Science and Pollution Research, 2021)

Multi-model ensemble simulated non-point source pollution based on Bayesian model averaging method and model uncertainty analysis - Huiliang Wang; Keyu Lu; Yulong Zhao; Jinxia Zhang; Jianli Hua; Xiaoying Lin (Environmental Science and Pollution Research, 2020)

Identification and fine mapping of spot blotch (Bipolaris sorokiniana) resistance gene Sb4 in wheat - Panpan Zhang; Guanghao Guo; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Beibei Li; Lingli Dong; Miaomiao Li; Rongge Wang; Chengguo Yuan; Huaizhi Zhang; et al. (Theoretical and Applied Genetics, 2020)

The total suitability of water yield and carbon sequestration under multi-scenario simulations in the Weihe watershed, China - Li Zeng; Jing Li; Keyu Qin; Jingya Liu; Zixiang Zhou; Yumeng Zhang (Environmental Science and Pollution Research, 2020)

Roles of sulfur compounds in growth and alkaline phosphatase activities of Microcystis aeruginosa under phosphorus deficiency stress - En Xie; Fangfang Li; Chaozi Wang; Wei Shi; Chen Huang; Keyu Fa; Xiao Zhao; Dayi Zhang (Environmental Science and Pollution Research, 2020)

Identification of long non-coding RNA p34822 as a potential plasma biomarker for the diagnosis of hepatocellular carcinoma - Cheng Wang; Tianyu Ren; Keyu Wang; Shaogeng Zhang; Shubin Liu; Hu Chen; Penghui Yang (Science China Life Sciences, 2017)

Effects of xeric shrubs on soil microbial communities in a desert in northern China - Yanfei Sun; Yuqing Zhang; Wei Feng; Shugao Qin; Zhen Liu; Yuxuan Bai; Ru Yan; Keyu Fa (Plant and Soil, 2017)

Changes in the long-term hydrological regimes and the impacts of human activities in the main Wei River, China - Hongbo Zhang; Qiang Huang; Qiang Zhang; Lei Gu; Keyu Chen; Qijun Yu (Hydrological Sciences Journal, 2016)

Genetic manipulation of a transcription-regulating sequence of porcine reproductive and respiratory syndrome virus reveals key nucleotides determining its activity - Haihong Zheng; Keyu Zhang; Xing-Quan Zhu; Changlong Liu; Jiaqi Lu; Fei Gao; Yan Zhou; Hao Zheng; Tao Lin; Liwei Li; Guangzhi Tong; Zuzhang Wei; et al. (Archives of Virology, 2014)

Molecular characterization, recombinant expression in Escherichia coli and biological activity of (S)-Tetrahydroberberine oxidase from Corydalis saxicola Bunt - Keyu Chen; Ji Ye; Chang Liu; Peng Di; JunFeng Chen; Ying Xiao; HuiLiang Li; WeiDong Zhang (Molecular Biology Reports, 2012)

Replicative senescence of human bone marrow and umbilical cord derived mesenchymal stem cells and their differentiation to adipocytes and osteoblasts - HuanChen Cheng; Lin Qiu; Jun Ma; Hao Zhang; Mei Cheng; Wei Li; Xuefei Zhao; Keyu Liu (Molecular Biology Reports, 2011)